2018
DOI: 10.24832/kapata.v14i2.534
|View full text |Cite
|
Sign up to set email alerts
|

Recent Rock Art Research on East Seram, Maluku: A key site in the rock art of West Papua and South East Maluku

Abstract: Gambar cadas di Indonesia mulai diteliti sejak sebelum abad 20. Sejumlah publikasi ilmiah sebelumnya mencatat keberadaan situs gambar cadas di Pulau Seram, Provinsi Maluku yaitu di tebing Sawai dan Sungai Tala. Survei arkeologi terkini di kawasan Seram Timur dan Seram Laut yang dilakukan oleh gabungan Tim Peneliti Indonesian-American berhasil menemukan Situs gambar cadas baru di pesisir Seram Timur. gambar cadas ini terlukiskan di permukaan dinding tebing bernama lokal tebing Watu Sika. Gambar cadas di Situs W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Research on rock art globally, especially in Indonesia and other Asian regions, began in the 18th and 19th centuries and is sure to continue with discovering new rock art sites (Tan, 2020). The distribution of rock art sites in Indonesia is known recorded in almost all islands, including Kalimantan, Sumatra, Sulawesi, Maluku Islands, Nusa Tenggara Timur Islands, and Papua (Arifin, 1992;Fauzi et al, 2019;Handoko et al, 2018;O'Connor, 2003;O'Connor, Mahirta, Tanudirjo, et al, 2018;Oktaviana et al, 2018;Widianto et al, 2017).…”
Section: Research History Of Rock Art In the Maluku Islandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on rock art globally, especially in Indonesia and other Asian regions, began in the 18th and 19th centuries and is sure to continue with discovering new rock art sites (Tan, 2020). The distribution of rock art sites in Indonesia is known recorded in almost all islands, including Kalimantan, Sumatra, Sulawesi, Maluku Islands, Nusa Tenggara Timur Islands, and Papua (Arifin, 1992;Fauzi et al, 2019;Handoko et al, 2018;O'Connor, 2003;O'Connor, Mahirta, Tanudirjo, et al, 2018;Oktaviana et al, 2018;Widianto et al, 2017).…”
Section: Research History Of Rock Art In the Maluku Islandsmentioning
confidence: 99%
“…The rock art on this site is depicted in anthropomorphic motifs, hand stencils, fish, boats, sun, geometric, and circles. 4) Watusika Site, Seram Laut Island, Seram Timur Regency, reported by Oktaviana et al (2018). Rock art on this site is in the form of anthropomorphic motifs, hand stencils, fish, boats, geometric, parallel lines, semicircles, curves, and crosses.…”
Section: Research History Of Rock Art In the Maluku Islandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most easterly of these have been recorded in West Papua in the karst districts of the Berau Gulf, Kaimana, the Baliem Valley (Arifin and Delanghe 2004), Triton Bay (Gonthier et al 2013), andMisool (Sulistyarto et al 2014). Others have been recorded in the Matgugul Kakun karsts on Buru Island (Ririmasse 2007) and at the Tala River in Seleman Bay on Seram (Oktaviana, Lape et al 2016). Other sites occur on the Kei Islands to the east of Seram (Ballard 1988;Setiawan 1994) and near Kupang in West Timor (O'Connor et al 2015), and in Timor Leste various sites with rock paintings near Tutuala and Baucau (O'Connor 2003), Baguia (O'Connor and Oliveira 2007) and the island of Atauro (Galipaud et al 2016) .…”
Section: Sitementioning
confidence: 99%
“…O'Connor et al (2017) reported that rock art discoveries have been recorded in at least 28 caves on Kisar Island and estimated that rock art has existed there since the Neolithic era and d in the early Bronze Age about 2500 years ago. At almost the same time Peter Lape (2017) found rock art sites in Seram Timur (Seram Laut) (Lape et al, 2017: 69;A. A. Oktaviana, Lape, & Ririmasse, 2016).…”
Section: Introductionmentioning
confidence: 99%